Outward FDI from India and its impact on the performance of firms in their home country - Indrajit Roy; K. Narayanan (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2016)
Indian OFDI has increased and diversified substantially in the last 10 years. This paper uses quantile difference-in-difference measure to estimate home country effects of the OFDI decision of Indian corporate on their firm level characteristics reflected in various financial/non-financial ratios. Quantile coefficients inform us about differential effects of OFDI on different segments of the probability distributions of these firm characteristics and also change in within group inequality. It is observed that in the Indian context, the 'home' effect of OFDI is a slow process and the true effect of OFDI is revealed as time progresses. Also the effects (dimension, intensity and significance level) of OFDI are not same across segments (top, median or bottom) of the distribution of the selected variables and effects are found to be mostly muted when they are analysed on the bases of mean of the distribution (i.e. general DiD effect). OFDI leads to (a) reduction of inequality of firms (b) improvement in R&D expense of firms except those firms with already relatively high expenditure (3rd quartile) (c) exports to sales initially improve for three years and then worsen for small firms (first quartile), however, for the mid-size firms (median) it worsens after one year and (d) median of operating ratio (expense/sales) as well as after tax profit margin (PAT/sales) worsened over the year.
hdl:10398/9295
Keywords: 330; Multinationales Unternehmen; Auslandsinvestition; Indisch; Unternehmenserfolg; Indien